Microwave irradiation-assisted isomerization of glucose to fructose over Mg/Al-doped lignin self-assembled nanospheres - Shan, Jianrong; Yang, Bowen; Su, Yaqiong; Chong, Gunhean; Abdullah, Luqman Chuah; Qi, Xinhua; Guo, Haixin (Elsevier, 2025)
Isomerization of glucose to fructose is a key step in achieving high value conversion of biomass. Lignin nanosphere (LN) showing hollow structure were successfully prepared using lignin oligomers as carbon precursors and self-assembly method. On this basis, Mg and Al were doped into lignin nanospheres by electrostatic and coordination interactions to obtain a heterogeneous catalyst (Mg x Al y /LN) with the coexistence of Brønsted base and Lewis acid. In this catalytic system, the synergistic effect of Al(OH) 3 and MgO as the active center of the catalyst promoted the formation of intermediates for the isomerization of glucose to fructose. DFT analysis show that Al(OH) 3 plays a greater role than MgO in promoting the isomerization of acyclic glucose to form fructose. When the Mg/Al ratio of 2:1, the yield of Mg 2 Al 1 /LN catalyzed isomerization of glucose to fructose under microwave irradiation can reach as high as 57.2 %, which could be reused for 5 times and still remain its initial activity. The activation energy was about 39.8 kJ/mol, which was lower than that of most heterogenous catalytic systems, showing good catalytic performance and potential for application.